Inflammatory effects of BaP1 a metalloproteinase isolated from Bothrops asper snake venom: leukocyte recruitment and release of cytokines - Fernandes, Cristina Maria (2006)
The inflammatory events induced by BaP1, a 22.7 kDa metalloproteinase isolated from Bothrops asper snake venom, were studied. BaP1 i.p. injection in mice induced a marked inflammatory cell infiltrate into peritoneal cavity of animals with predominance of neutrophils in the early phase followed by mononuclear cells in the late period. Inhibition of enzymatic activity of BaP1 by chelation with EDTA resulted in a drastic reduction of this effect. In addition, BaP1 induced a significant increase of blood neutrophil numbers before its accumulation in peritoneal cavity, thus suggesting a stimulatory action of BaP1 on mechanisms of cell mobilization from bone marrow reserve compartments. A reduction in the number of neutrophils was observed in the exudate when antibodies against LECAM-1, CD18 and LFA-1 were used, suggesting the involvement of these adhesion molecules in the effects of BaP1. In contrast, there was no effect with antibodies against ICAM-1 and PECAM-1. Moreover, a conspicuous increment in the levels of IL-1 and TNF-alpha, but not of LTB4, was observed in peritoneal washes collected from mice injected with BaP1. It is concluded that BaP1 induces in vivo a marked leukocyte influx, which parallels an increased number of these cells in the blood, and is associated to the expression of specific leukocyte adhesion molecules and release of chemotactic inflammatory cytokines. Since BaP1 is a P-I class metalloproteinase, these results indicate that the proteolytic domain of metalloproteinases per se can trigger specific inflammatory events.